IMPLEMENTASI DATA MINING UNTUK MEMPREDIKSI JUMLAH PEREDARAN KENDARAAN RODA EMPAT DI KOTA TERNATE MENGGUNAKAN METODE C.45 - Sahriar Hamza (Fakultas Teknik UMMU, 2019)
The purpose of the research is to determine the growth rate of Four-Wheel Vehicles in Ternate. The implementation of data mining using the C.45 Algorithm aims to predict the circulation of four-wheeled vehicles in Ternate through the year as an attribute in determining a value. The results are obtained from the gain and ratio through the classification process toward brand and number of vehicles based on the year. The data shows that there was an increase in the number of circulation of four-wheeled vehicles in Ternate in 2013 to 2016, which was 0.91%. This will predict to increase in the following year.